KOMPONEN EVALUASI LINGKUNGAN BELAJAR KLINIK, SUPERVISI DAN DOSEN PERAWAT - Fahruddin Kurdi; Pepin Nahariani; Ratna Puji Priyanti (Universitas Nahdlatul Ulama Surabaya, 2018)
Ners education in Indonesia is integrated between academic learning and clinical learning. The learning environment of conducive clinical practice is highly conquered. The environment in which, the atmosphere that supports students to learn. Things that are not obtained by nursing students in academic learning environment will be obtained at the time of clinical learning practice. To identify students' perceptions of the clinical practice learning environment and supervision of the hospital-based clinical practice learning process in Indonesia and the influencing factors. The design of this study used correlational analytic survey method with cross-sectional approach, with sampling technique of convinience sampling. The study population is Ners educational institution. The sample of research is 3 institution of Ners education organizer in East Java. Instruments using ELBKS + D Indonesian version. Respondents aged between 20 to 28 years, 20-22 years of 89 (54.3%), female sex of 115 (70.1%). Medical Surgical Nursing became the most widely practiced stages of 62 (37.8%). That the practical stages are significantly related to the role of the lecturer on the scale of ELBKS + D with r-value = 0.158 and ρ-value = 0.044. Discussion: Nursing students consider that the success of clinical teaching practice is determined primarily by the content of supervisory relationships and the role of nursing lecturers. The nurse lecturer role sub variable in ELBKS + D has correlation with student's precursor stages.